Study of Waves, Currents and Coastline Changes in North Rupat Sub-District, Bengkalis Regency, Riau - Fathurrahman, Febri; Mubarak, Mubarak; Nurrachmi, Irvina; Rifardi, Rifardi; Ilahi, Ilham (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
The Malacca Strait, between the island of Sumatra and the Malaysian Peninsula, is classified as an international strait. One of the Indonesian islands in the Malacca Strait is Rupat Island, which is the outermost small island of the Indonesian territory and has a sub-district directly facing the Malacca Strait, namely North Rupat Sub-district resulting in the phenomenon of shoreline change in this area. The location that became the research object is the coastal waters of the North Rupat District. The research aimed to investigate the coastline changes in Rupat Utara over the past 20 years and analyze the physical oceanographic factors affecting the area. The research method used in the research is survey methods. Primary data collected were wave, tidal, and sediment data. Sediment sampling was carried out using a sediment grab at the research stations, with each station being sampled three times. The sediment samples were collected at intervals of 50 meters between sampling points at each station. The results of the analysis of changes in the coastline of North Rupat District carried out using DSAS, and it can be seen that in the period 2003 to 2023, there was a change in the coastline, which was dominated by the accretion process with the highest accretion value at 252.80 m, the lowest abrasion value was -111.29 m, and an EPR value of 2.20 m/year. The current velocity and wave height in these waters are categorized as low. The sediment fraction in this area falls into the sand and mud categories